Diseño de un modelo práctico de coordinación interinstitucional para apoyar el fortalecimiento de la producción sostenible en la Región Huetar Norte. - Céspedes-Obando, Francisco (2025)
The project Design of an inter-institutional coordination model to support the strengthening of sustainable production in the Northern Huetar Region proposes the design and validation of a coordination model for the joint participation of institutions in the region that directly and indirectly support business management and the development of agricultural and value-added production in the Northern Huetar Region. These institutions include the Ministry of Agriculture and Livestock (MAG), the National Learning Institute (INA), the Rural Development Institute (INDER), among others. The project was externally funded by Fundecooperación for Sustainable Development and was operationally managed with the assistance of the Costa Rica Institute of Technology Foundation (FUNDATEC). This article presents the proposed model and the main considerations to take into account for its implementation.